The predictors of voluntary participation in pulmonary tuberculosis screening program: a study in a suburban community of southern Thailand - Kongkamol, Chanon; Chintrakul, Apinya; Horsiritham, Kanakorn; Kiranantawat, Nantaka; Nirattisaikul, Sitang; Sungsiri, Jitpreedee; Sathirapanya, Pornchai; Sathirapanya, Chutarat; Boonma, Koontidar; Chowwanapoonpohn, Tuck; Nuiman, Paradon; Supunthuchaikul, Jekita; et al. (Frontiers in Public Health, 2024)
Background: Health belief model (HBM), baseline health condition, and socio-cultural factors impact the decision to participate in a tuberculosis screening program. Methods: This cross-sectional and descriptive study was done in 'Kao Taew' community dwellers aged 18 years and up who voluntarily underwent the provided pulmonary tuberculosis (PTB) screening by chest radiographies (CXRs). The level of individual HBM domain perception, attitudes towards PTB prevention, and regularity of PTB prevention practices of the participants were evaluated. The significantly associated or correlated factors from the demographic characteristics, individual HBM domain perception and attitudes towards PTB prevention with regularity of PTB prevention practices from univariate analysis were further analyzed by multiple linear regression (p<0.05) to determine the independent significant predictors of PTB prevention practices.Results: Among 311 participants comprising 65% female, 57.9% aged ≥ 65 years, and 67.2% had an underlying disease. The study participants had high level of perception of each HBM domain except for low perception of barrier. Also, high level of attitudes towards PTB prevention and high regularity of PTB prevention practices were found. The multiple linear regression analysis revealed that perceived benefits of PTB screening (Beta=0.20 (0.04, 0.36) p= 0.016) and acquiring an underlying diseases (Beta=1.06 (0.38, 1.73), p= 0.002) were significant predictors for PTB prevention practices, while belief in Islam was a reverse predictor (Beta= -0.84 (-1.47, -0.21), p= 0.010).Conclusions: Level of perception of individual domain of HBM, health status and religious belief significantly predicted the voluntary participation in PTB screening programs. Careful consideration by integration of the relevant health psychology, physical, and socio-cultural factors is crucial for planning a health screening program.